Auditory stimulus for children with high functioning autism: towards reducing developmental disorders and inattentive attitudes - Ong, Jessica Hai Liaw; Dani, Noor Aina; Johari, Ahmad Zaidi (American-Eurasian Network for Scientific Information, 2013)
Preliminary findings in several works have described that children with high functioning autism frequently show hypersensitivity to auditory stimulus. We seek the answer by using auditory stimulus interventions in our time series research. Interventions were assigned alternately to weekly 30 minutes learning session each for musical auditory stimulus followed by musical songs auditory stimulus for 8 weeks without washout period. The aim is to detect trends such as reductions in developmental disorders and inattentive attitudes among participants. Targeted variables for developmental disorders are responsiveness in language, social, cognitive, and emotion. Cognitive and emotion responsiveness are included as a new variables which has not been reviewed by any of the authors referred to. The participants are 5 boys (mean age 12.2 years) with a primary diagnosis of HFA and students of special education programme for children with autism conducted by The National Autism Society of Malaysia (NASOM). The result shows that musical songs auditory stimulus is more beneficial to children with high functioning autism in reducing their developmental disorders with the highest responsiveness both in language and cognitive variables. The same stimulus is also regarded as the more valid intervention in measuring the participants’ attentive attitudes by showing a 43 percent reduction with a ratio of 1 in musical auditory stimulus equal to 2 in musical song auditory stimulus. Nevertheless, both interventions cannot reduce the autistic aloneness, a deficit in the social skill of children with high functioning autism. A possible beneficial future study on the effect of musical songs auditory stimulus in children with Rett syndrome is strongly suggested.